A first report of tumour-tracking radiotherapy with helical tomotherapy for lung and liver tumours: A double case report. (June 2021) - Okada, Wataru; Doi, Hiroshi; Tanooka, Masao; Sano, Keisuke; Nakamura, Kenji; Sakai, Yusuke; Shibata, Mayuri; Tanaka, Masahiro
There are only a limited number of previous reports on clinical cases using tumour tracking with tomotherapy. Therefore, we present two cases of patients treated with tumour tracking with tomotherapy. First, a 74-year-old man with an inoperable lung cancer type T1bN0M0 underwent stereotactic body radiotherapy at a total dose of 48 Gy in four fractions. Second, a 68-year-old man with hepatocellular carcinoma with a portal venous tumour thrombosis and history of liver stereotactic body radiotherapy with fiducial marker implantation received radiotherapy at a total dose of 48 Gy in 20 fractions. The results of patient-specific quality assurance and tracking radiotherapy were sufficient to irradiate tumours. Tumour tracking with tomotherapy successfully delivered radiation in a total of 24 treatment fractions in both patients. Tumour tracking with tomotherapy is feasible in lung and liver cancer treatment. This study's findings suggest the clinical use of tumour tracking with tomotherapy.